PUMP.FUN AND MEME-COINS - Dan Valeriu VOINEA (Annals of the University of Craiova for Journalism, Communication and Management, 2025)
Launched in 2024, Pump.fun enabled the instant minting and trading of millions of tokens, generating hundreds of millions in fee revenue by capitalizing on speculative frenzy. While positioned as a form of participatory culture and financial democratization, the platform's ecosystem exhibited characteristics analogous to Ponzi schemes